2010
DOI: 10.1159/000318743
|View full text |Cite
|
Sign up to set email alerts
|

Non-Proteolytic Aeroallergens from Mites, Cat and Dog Exert Adjuvant-Like Activation of Bronchial Epithelial Cells

Abstract: Background: Exposure to seasonal or indoor allergens may cause sensitisation and development of allergic airway diseases. We have previously demonstrated that the non-proteolytic major house dust mite (HDM) allergen Der p 2 stimulates pro-inflammatory responses in bronchial epithelial cells. We aimed to determine if other clinically relevant non-proteolytic aeroallergens originating from HDMs, storage mites, cat, dog, birch and timothy also activate respiratory epithelial cells. Methods: Cultures of human bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
0
20
1
1
Order By: Relevance
“…The most likely lung cells regulated by GSTM1 are bronchial epithelial and smooth muscle cells that express GSTM1 (7) and are capable of generating proneutrophilic cytokines after exposure to allergens (35). We did not find regulation by allergens of other proneutrophilic cytokines previously associated with asthma, including IL-17, a T cell-dependent cytokine (26); IL-33, a chromatin-associated nuclear cytokine from the IL-1 family of cytokines (27); and CXCL1 (36).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The most likely lung cells regulated by GSTM1 are bronchial epithelial and smooth muscle cells that express GSTM1 (7) and are capable of generating proneutrophilic cytokines after exposure to allergens (35). We did not find regulation by allergens of other proneutrophilic cytokines previously associated with asthma, including IL-17, a T cell-dependent cytokine (26); IL-33, a chromatin-associated nuclear cytokine from the IL-1 family of cytokines (27); and CXCL1 (36).…”
Section: Discussionmentioning
confidence: 64%
“…However, the GSTM1-dependent restraining mechanism could be disrupted in the atopic asthmatic airways as a result of down-regulation of the transcription factor nuclear factor (erythroid-derived 2)-like 2 (38, 39) controlling expression of GSTM1 (40). Airway epithelial cells could be particularly affected as they express GSTM1 (7) and are capable of generating robust proneutrophilic signals after allergen stimulation (35). A tight regulation of stress-signaling pathways would suggest the presence of an alternative inhibitory mechanism in GSTM1 2 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OGG-1 siRNA significantly inhibited IL-2, IL-4, and IL-17, while enhancing IFN-γ. It is worth noting that there are differences in cytokine expression between the OVA and HDM models as HDM extracts induce inflammation, largely as a result of their protease activities (65). Nevertheless, our HDM in vitro model identified a potential regulatory role for OGG-1 in ROS levels because anti-oxidants prevented the increase in ROS and OGG-1 levels following HDM challenge.…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is the bronchial epithelium's hyporesponsiveness towards Gram-positive bacteria, due to low expression of TLR2 and a lack of expression of CD36, which mediates the phagocytosis of Gram-positive bacteria [35,36]. Others have shown that certain microorganisms or aeroallergens may function as adjuvants for epithelial activation in both protease-dependent and independent manners [37,38]. The airway epithelium also maintains a steady-state condition by producing anti-inflammatory cytokines, such as TGF-β and indoleamine 2,3-dioxygenase, which suppress T cell-mediated immunity, as well as the activation of antigen-presenting cells [34,39].…”
Section: The Airway Epitheliummentioning
confidence: 99%